Assessment of physicochemical properties of Lafarge cement towards achieving a sustainable society - Abiodun Oluwatosin Adeoye; Rukayat Oluwatobiloba Quadri; Olayide Samuel Lawal (Proceedings of the Nigerian Society of Physical Sciences)
Conducive shelter is one of the basic needs of life, and in this modern society, large numbers of livable structures are made of cement. The number of cases of collapsed structures/buildings in Nigeria has been on the increase in recent times, reported in cities like Lagos, Ibadan, Abuja, Port Harcourt, etc. There is an urgent need to find lasting solutions to tackle structural/building challenges arising from the use of cement. The manufacturing of cement is a continuous process, necessitating ongoing monitoring of the quality of Ordinary Portland Cement, as recommended by the Standard Organisation of Nigeria (SON). The study assessed the physicochemical and mechanical properties of four brands of Lafarge cement named Elephant Classic Supaset, Powermax, and Standard grade using standard procedures. The cement analysis reveals that the SiO2 content increases with the grade of cement, with the highest value of 20.46% in 52.5-grade cement. Similarly, higher grades of cement demonstrate greater values in Al2O3, Fe2O3, and MgO, indicating enhanced material composition for higher strength applications. Most of the parameters analyzed (%SiO2, %SO3, 28-Day strength, and % oxides of metal) align with the standards of SON and ASTM. It can be concluded that building failure due to the use of these cements could be linked to the use of nonprofessional builders, other fake materials, and corruption by contractors.